Agua: geopolitica internacional e propostas para um estudo integrado de bacias hidrográficas - Souza, George Taylor De; Luiza Leonardi Bricalli; Marcelo Almeida Moreto; Silma Lima Ferreira; Sueli Calente (Geografares, 2002)
DOI: 10.7147/GEO3.1117